Factors Influencing the Implementation of Music Activities by Government Preschool Teachers in Selangor - Kwan, Shyan Shwu (2006)
This study sought to identify the factors influencing the implementation of music by Selangor preschool teachers with reference to their years of teaching experience, perceptions, self-efficacy and support. It also evaluates the implementation of music which is the type of music equipment used and type of music activities the teachers’ implement and frequency of implementation. It is essential to understand the factors that enhance or undermine teachers’ attempts to implement music as little data exists on the factors. Questionnaires were distributed to 138 preschool teachers in various districts in Selangor to generate the data required for this study. This study utilized a variety of analysis techniques on the data obtained, ranging from descriptive analysis to Pearson productmoment correlation coefficient analysis and multiple linear regression analysis.The research findings revealed that the respondents highly perceived on the important role music play in personal and social development; in the development of music skills and knowledge; in classroom management; and in miscellaneous benefits. The level of self-efficacy of the respondents in implementation of music was moderate. Results from the questionnaire data indicated that the level of support for the respondents was high. Most preschools were in line with the preschool curriculum requirements of music equipment used for teaching and learning facilitation. The level of implementation for music appreciation activities was moderate. Similarly the level of implementation for singing activities was also moderate. For creative movement activities, the level of implementation was high with many respondents having a large open area for music movement activities. The level of implementation of music for overall music activities which were music appreciation, singing and creative movement was moderate. Statistical test revealed that there was no relationship between years of teaching experience and implementation of music. The relationship between support and implementation of music was low. Both the relationship between teachers’ perception and implementation of music and the relationship between self-efficacy and implementation of music were moderate. Further statistical test indicated that self-efficacy was the most important factor which influenced the implementation of music in the classroom. However, the study revealed that there were some respondents who did not have the confidence in their abilities in teaching music. Therefore, pre-service preschool training programs need to be designed in such a way that it can develop skills and concepts more thoroughly while helping them to develop their abilities to use music activities combined with other subjects or activities. Lastly, it is hoped that the findings and recommendations of this study will contribute towards improving the implementation of music by preschool teachers in their classroom.